UV light pan traps for collecting aquatic insects - Calor, Adolfo Ricardo; Mariano, Rodolfo (EntomoBrasilis, 2012)
A simple, inexpensive light trap is described for collecting night-flying insects. The components for constructing the light trap are described and the advantages and disadvantages for collecting different taxa of aquatic insects are discussed. Armadilha Luminosa para Coleta de Insetos Aquáticos Resumo. Armadilha luminosa simples e de baixo custo é apresentada para coleta de insetos noturnos. Os componentes necessários para a construção da armadilha luminosa são descritos, assim como suas vantagens e desvantagens são discutidas.